The interlinkage of brand image and the combined effect toward satisfaction, trust and brand loyalty in the five star hotel segment / Mohd Raziff Jamaluddin - Jamaluddin, Mohd Raziff (2017)
Before the shift in focus towards brands and the brand building process, brands were just another step in the whole process of marketing to sell products. The brand has not been treated significantly in the marketing or developing the product or services. The brand has evolved from merely a symbol or logo into creating a memorable experience. It is tough to measure the success story of a strong brand, but a visionary company always builds and maintains brand as its greatest asset. The progress of branding literature has changed dramatically and always subject to constant review and redefinition. There is no particular theory to express the quality of a brand thus provide limitless opportunities for new theories to be developed in this area. Taking the five star hotel segment as the research setting, the present study embarks on the research journey to prove the interlinkage between brand image components in particular brand experiential value, brand personality and brand social responsibility, and the combined effect toward satisfaction, trust and brand loyalty. From extensive literature search, very limited studies had examined the effect of the brand image toward hospitality industry. The hospitality industry has a great potential to expand further looking at the way the industry performed in the past few years. This study is not only significant for knowledge creation but also to the future industry direction. This study offers a new dimension in understanding guest's perception of superiority. Being the upscale market, five-star hotel segment fulfills the lifestyle and preference of the knowledgeable market segments thus recognizing the customer's satisfaction will result in a formation of trust and brand loyalty. To prove this relationship, this study employed quantitative analysis using structural equation modeling. Purposive sampling was used to collect data from 631 sample size. A total of 41 items were listed in the self-reported questionnaire that had been distributed within three months data collection process. 70.7 percent response rate was recorded for the data collected. Results showed that brand image is significant for the five-star hotel to ensure brand loyalty. Apart from that, no multiple roles of mediating played by the outcome variables listed in the study. This study concluded that the sequence of effect starting from brand image to satisfaction, trust and brand loyalty must be fulfilled first before the formation of a new relationship took place.